2018
DOI: 10.4077/cjp.2018.bag584
|View full text |Cite
|
Sign up to set email alerts
|

Importance of PLC-Dependent PI3K/AKT and AMPK Signaling in RANTES/CCR5 Mediated Macrophage Chemotaxis

Abstract: Regulated upon activation, normal T cell expressed, and secreted (RANTES), also known as chemokine ligand 5 (CCL5), has been reported to facilitate macrophage migration, which plays a crucial role in tissue inflammation. The aim of this study is to investigate the characteristics and underlying mechanism of RANTES on macrophage chemotaxis under physiological and pathological conditions. The study was conducted on macrophage RAW264.7 cell and bone marrow-derived macrophages (BMDM) isolated from CCL receptor 5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Glucose uptake was determined, as previously reported [ 41 ]. Briefly, C2C12 myotubes attached to the plate were incubated in 1 mL of media buffer supplemented with 138 mM NaCl, 1.85 mM CaCl2 1.3 mM MgSO4, 4.8 mM KCl, 50 mM HEPES pH 7.4 and 0.2% (W/V) BSA for 2 h. Then, 250 mL of 2-deoxy-H 3 -glucose (1 mCi/mL) was added to the well, and the cells were incubated for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Glucose uptake was determined, as previously reported [ 41 ]. Briefly, C2C12 myotubes attached to the plate were incubated in 1 mL of media buffer supplemented with 138 mM NaCl, 1.85 mM CaCl2 1.3 mM MgSO4, 4.8 mM KCl, 50 mM HEPES pH 7.4 and 0.2% (W/V) BSA for 2 h. Then, 250 mL of 2-deoxy-H 3 -glucose (1 mCi/mL) was added to the well, and the cells were incubated for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The chemokine ligand 5 (CCL5) also known as RANTES (regulated upon activation, normal T cell expressed, and secreted) is the natural ligand for CCR5 ( Chien et al., 2018 ), whereas the CXC-chemokine ligand 12 (CXCL12), also known as SDF-1 (stromal cell-derived factor 1) is the natural ligand for CXCR4 ( Smith et al., 2017 ). Inhibition of either CCR5 or CXCR4 leads HIV to shift to a more virulent dual-tropic strain.…”
Section: Introductionmentioning
confidence: 99%
“…Further, while not specific to CCR5, studies have suggested that the release of G Ī²Ī³ , rather than G Ī±i is essential for chemotaxis mediated by G Ī±i -coupled receptors [ 195 , 229 ]. Both the PLCĪ² and PI3K signaling cascades mediate the chemotactic response to CCR5 binding by activating a number of Ser/Thr protein kinases, particularly members of the PAK and FAK families, in macrophages [ 230 , 242 , 273 , 276 ] and T-lymphocytes [ 213 , 214 , 276 ]. Signaling via the PLCĪ² signaling cascade also activates MAPKs [ 221 , 267 ], which is associated with the production of inflammatory mediators [ 31 , 267 , 277 ] and chemotactic responses [ 223 , 278 , 279 ].…”
Section: Chemokine Receptorsmentioning
confidence: 99%